(untitled) ("Temas Sociais" Journal, 2022)
The Continued Care National Network (RNCCI - Rede Nacional de Cuidados Continuados Integrados), results from a partnership between Ministério do Trabalho e da Solidariedade Social and Ministério da Saúde to ensure rehabilitation, readaptation ofc social and family reintegration of people in a situation of dependece. It´s a policy that State regulates, through agreements and partnerships with the third sector and private entities. The pandemic, as an unprecedented public health crisis, has brought enormous challenges to the protection of the well-being and citizens human rights. The study focuses on the intervention of social work in the Long-Term and Care Units (ULDM - Unidades de Longa Duração e Manutenção) as well as the strategies used during the pandemic, with the aim of offering a vision of the economic and social vulnerabilities of the patients of ULDM inserted in the Inter-municipal Community of the West of Portugal (OesteCIM). The work is based on a qualitative methodology using a semi-directive interview technique. The study demonstrates that, of the 180 ULDM patients, 81 are considered "social cases" which, in the words of the interviewees, are patients with a reduced family and economic support. The persistence and resilience of Social Workers and their permanent attempt to find a social solution for these patients is highlighted, as well as the family involvement to maintain affective bonds. It was reported the most harmful consequence caused by the impact of the pandemic was the absence of visits.